Risk Sharing through Financial Markets with Endogenous Enforcement of Trades - Thorsten Koeppl (Queen's University, Department of Economics, 2004)
When people share risk in financial markets, intermediaries provide costly enforcement for most trades and, hence, are an integral part of financial markets' organization. We assess the degree of risk sharing that can be achieved through financial markets when enforcement is based on the threat of exclusion from future trading as well as on costly enforcement intermediaries. Starting from constrained efficient allocations and taking into account the public good character of enforcement we study a Lindahl-equilibrium where people invest in asset portfolios and simultaneously choose to relax their borrowing limits by paying fees to an intermediary who finances the costs of enforcement. We show that financial markets always allow for optimal risk sharing as long as markets are complete, default is prevented in equilibrium and intermediaries provide costly enforcement competitively. In equilibrium, costly enforcement translates into both agent-specific borrowing limits and price schedules that include a separate default premium. Enforcement costs - or, equivalently, default premia - increase borrowing costs, while interest rates per se depend on the change in enforcement over time.
Keywords: C73; D60; G10; H41; K42; 330; Limited Commitment; Enforcement Intermediaries; Lindahl-equilibrium; Endogenous Borrowing Constraints; Finanzmarkt; Wertpapierhandel; Risikomanagement; Liquiditätsbeschränkung; Beschränkte Haftung; Theorie